2014
DOI: 10.1007/s00277-014-2233-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics for once-daily modified release formulation of tacrolimus hydrate in unrelated hematopoietic stem cell transplantation

Abstract: A once-daily modified release formulation of oral tacrolimus (Tac QD) has been developed in response to the problem of nonadherence. However, there have been no data available about the efficacy of Tac QD conversion from intravenous Tac (Tac i.v.) in allogeneic hematopoietic stem cell transplantation (allo-SCT). We analyzed the pharmacokinetics (PK) of Tac QD in allo-SCT recipients. A total of 10 patients with hematological malignancies who received allo-SCT from unrelated donors were enrolled. Patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Tacrolimus has a narrow therapeutic window in HSCT, and Yano et al [ 41 ] reported that the modification of Tac-QD to maintain a whole tacrolimus C 0 above 7.5 ng/mL may be as effective as Tac-BID, and no patient developed grade III–IV acute GVHD. On the other hand, we demonstrated that nephrotoxicity of tacrolimus may increase when tacrolimus C 0 was above 10.1 ng/mL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus has a narrow therapeutic window in HSCT, and Yano et al [ 41 ] reported that the modification of Tac-QD to maintain a whole tacrolimus C 0 above 7.5 ng/mL may be as effective as Tac-BID, and no patient developed grade III–IV acute GVHD. On the other hand, we demonstrated that nephrotoxicity of tacrolimus may increase when tacrolimus C 0 was above 10.1 ng/mL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is generally given by IV infusion at a dose of 0.03 mg kg −1 day −1 initially and covert to oral administration with a ratio of 1:3 to 1:5 thereafter ( Brunet et al, 2019 ). In most clinical trials/retrospective studies, the target C 0 concentration of tacrolimus for GVHD treatment is 10–20 ng mL −1 ( Mori et al, 2012 ; Yano et al, 2015 ; Kanda et al, 2016 ). A study on children with HSCT found that during the first 4 weeks of continuous infusion of tacrolimus, an average concentration of ≤7 ng mL −1 would increase the risk of aGVHD and reduce the survival rate after transplantation ( Watanabe et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…During a day, normal blood concentrations can rise to 20 ng/mL. 19 , 20 In addition, CNIs-induced neuropsychiatric symptoms have been described in patients with therapeutic blood concentrations. 21 - 23 …”
Section: Deliriummentioning
confidence: 99%